Morning blood pressure surge: pathophysiology, clinical relevance and therapeutic aspects - Bilo G; Grillo A; Guida V; Parati G (Dove Medical Press, 2018)
Grzegorz Bilo,1,2 Andrea Grillo,1,2 Valentina Guida,1,2 Gianfranco Parati1,2 1Department of Medicine and Surgery, University of Milano-Bicocca, Milan, Italy; 2Cardiology Unit, Department of Cardiovascular, Neural and Metabolic Sciences, San Luca Hospital, IRCCS Istituto Auxologico Italiano, Milan, Italy Abstract: Morning hours are the period of the day characterized by the highest incidence of major cardiovascular events including myocardial infarction, sudden death or stroke. They are also characterized by important neurohormonal changes, in particular, the activation of sympathetic nervous system which usually leads to a rapid increase in blood pressure (BP), known as morning blood pressure surge (MBPS). It was hypothesized that excessive MBPS may be causally involved in the pathogenesis of cardiovascular events occurring in the morning by inducing hemodynamic stress. A number of studies support an independent relationship of MBPS with organ damage, cerebrovascular complications and mortality, although some heterogeneity exists in the available evidence. This may be due to ethnic differences, methodological issues and the confounding relationship of MBPS with other features of 24-hour BP profile, such as nocturnal dipping or BP variability. Several studies are also available dealing with treatment effects on MBPS and indicating the importance of long-acting antihypertensive drugs in this regard. This paper provides an overview of pathophysiologic, methodological, prognostic and therapeutic aspects related to MBPS. Keywords: morning blood pressure surge, ambulatory blood pressure monitoring, cardiovascular risk, blood pressure variability